2009
DOI: 10.3329/jhpn.v27i2.3371
|View full text |Cite
|
Sign up to set email alerts
|

oxytoComparison of Domiciliary and Institutional Delivery-care Practices in Rural Rajasthan, India

Abstract: A retrospective cross-sectional survey was conducted to assess key practices and costs relating to home-and institutional delivery care in rural Rajasthan, India. One block from each of two sample districts was covered (estimated population-279,132). Field investigators listed women who had delivered in the past three months and contacted them for structured case interview. In total, 1,947 (96%) of 2,031 listed women were successfully interviewed. An average of 2.4 and 1.7 care providers attended each home-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 12 publications
5
62
0
Order By: Relevance
“…Evidence from a qualitative study revealed that several women were discharged very early from facilities after delivery, often within 2-3 hours, without any advice about postnatal care or initiation of breastfeeding (17). This has been corroborated by a survey in two districts of Rajasthan (reported separately in this issue of the Journal), which showed that 14% of 632 women who had an institutional vaginal delivery were discharged within six hours of delivery, and 70% before 24 hours had elapsed (18). Results of a verbal autopsy study of all 57 deaths in two rural blocks showed that five deaths had occurred among women who were discharged within 1-2 hour(s) of delivery, one from postpartum haemorrhage and four from sepsis (19).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Evidence from a qualitative study revealed that several women were discharged very early from facilities after delivery, often within 2-3 hours, without any advice about postnatal care or initiation of breastfeeding (17). This has been corroborated by a survey in two districts of Rajasthan (reported separately in this issue of the Journal), which showed that 14% of 632 women who had an institutional vaginal delivery were discharged within six hours of delivery, and 70% before 24 hours had elapsed (18). Results of a verbal autopsy study of all 57 deaths in two rural blocks showed that five deaths had occurred among women who were discharged within 1-2 hour(s) of delivery, one from postpartum haemorrhage and four from sepsis (19).…”
Section: Resultsmentioning
confidence: 68%
“…For example, in 10 districts of Rajasthan, only 39% of the CHCs and 0.5% of the PHCs provided MTP services in 2007-2008 (data collected by ARTH from offices of health authorities in 2007-2008). A few doctors managed to receive MTP training in the state—1,056 doctors were trained during 1971-2002, with an average of 35 doctors per year (22). The availability of abortion services in the private sector also is poor—a review of services has revealed that 428 certified private facilities provided abortion services in 2002 (23), or an average of 0.67 certified private facilities per 100,000 population.…”
Section: Resultsmentioning
confidence: 99%
“…The study done in Baitadi district shows that 28% of mother had not any ANC visit [5]. The study done in Rajasthan, India shows that majority 88% of respondent have ANC visit two or more than 2 times [6]. Similarly study conducted on Darjeeling districts shows 66.5% mother had two or more than 2 times ANC visit [7].…”
Section: Discussionmentioning
confidence: 99%
“…Direct cost incurred by the end user was considered as out-ofpocket (OOP) expenditure and both the terms were used interchangeably. 7 …”
mentioning
confidence: 99%
“…6,7 Poor households often resort to borrow cash or sell assets to meet the health expenditure. 8,9 The household costs are broadly categorized as direct cost and indirect cost.…”
mentioning
confidence: 99%